Breast cancer metastasis to the stomach confirmed using gastroscopy: A case report - TAN, LINSHEN (D.A. Spandidos, 2014)
Breast cancer metastasis to the stomach is relatively rare. Unlike infiltrating ductal carcinoma, invasive lobular carcinoma (ILC) has a high tendency to metastasize to the stomach. The present study reports a case of a 53-year-old female who had undergone a modified radical mastectomy of the left breast for ILC eight years previously and presented at the clinic seeking treatment for epigastric discomfort from sour regurgitation and belching that had persisted for one month. Gastroscopy revealed multiple apophysis lesions in the stomach, which were diagnosed as metastatic tumors to the stomach. The diagnosis was further established using histological and immunohistochemical analyses for gross cystic disease fluid protein-15, cytokeratin (CK) 7 and CK20. The patient was treated with systemic chemotherapy without surgery. During the treatment, two gastroscopy procedures revealed that the apophysis lesions in the gastric body had narrowed significantly. Few cases of breast cancer metastasizing to the stomach have been reported, particularly those that have been confirmed using gastroscopy. The present study reports a case of breast cancer metastasis to the stomach to raise awareness of the condition.